The satisfaction of student and teacher at the Computer Engineering Department for using Online Examination System - Mekthanavanh, Vinath; Siphada, Vatthanaly; Souchaleun, Xaysavath; Yang, Xang; Khongketh, Thongphet (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The objective of this paper is to study the satisfaction of teachers and students by implementing the online examination system at the Department of Computer Engineering, Souphanouvong University. This system has been trying out in the final exam of the first semester of academic year 2019 - 2020. The samples used in this study are 8 teachers and 69 students by using close-ended and open-ended questionnaires to collect the data and SPSS software have been utilized for getting statistic values. The results indicated that the statistic tests of teachers, we found the most of participant is male who aged between 31-35, with 5-10 years of working experience. In their examination, the multiple choices and short answer of question type have been used. The aim of using an online examination system is to reduce the budget and to avoid using papers and other materials. According to the implementation of the system, teachers can collect the score of examination around 1-3 days. The system is faster, convenient, and given collect score of the answers of an examination. The total average values of the satisfaction are at the level of very satisfied with 4.01. The satisfaction of the other terms in the system such as the convenience, fasting, and the time of collecting scores are at the level of most satisfied. The result of student showed that 40.6% is male in the third grade with the age between 21-24 ages. The thinking of using an online examination is that the system is modern by offering convenient way and and also the score given by system is believable. After the exam have been submitted, they can immediately know the result, by comparing the current using system is that they may wait about 3 weeks. The 53.6% of students worried about the internet signals provided by Souphanouvong University with sometime unstable signals has been occurring. The 29% of them have worried about the surrounding environment in examination rooms. Therefore, the 69.6% of students agreed to use their own internet in their mobile for connecting the online examination system and also agreed to implement the online examination system to replace the current system by given average statistic value of very satisfaction is 3.74. The student almost has satisfaction in the quality of the online system. For the materials and internet signals are at the level of middle satisfaction.